2006
DOI: 10.1300/j083v48n01_13
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Aging Prepared Community

Abstract: This paper reports on a collaborative process to create an "aging prepared community" in a four county region. The process benefited from a generous grant from the John A. Hartford Foundation that supported an 18 month planning period which included input from service providers and a vast array of aging persons and their families, including particular efforts to reach underserved populations from multicultural, inner- city and rural communities. Under the umbrella of the Elder Network of the Capital Region, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…In our study, we observed that transportation was actually more likely to be perceived as a problem in the urban core areas (10.9%) as compared to more rural areas (5.2% or less). Similar to other studies we observed that outside of the urban core, a lack of adequate facilities was reported as a problem to accessing programs and resources [ 28 , 30 , 40 43 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, we observed that transportation was actually more likely to be perceived as a problem in the urban core areas (10.9%) as compared to more rural areas (5.2% or less). Similar to other studies we observed that outside of the urban core, a lack of adequate facilities was reported as a problem to accessing programs and resources [ 28 , 30 , 40 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…A few studies have focused on rural populations and older consumer needs [ 13 , 28 – 39 ]. One early study by Scala [ 28 ] reported that “older people living in rural areas face unique challenges, not only in accessing benefits and services, but also in gathering information about programs that can help them.” Rural and inner city areas have decreased access to services in New York State [ 30 ]. In a retrospective chart reviews (2004) rural patients were less likely to meet hemoglobin A1c and low-density lipoprotein cholesterol goals, less likely to receive screening and preventative services such as lipid profiles, eye examinations, microalbumin screening, aspirin therapy and vaccinations as compared to urban patients [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, notwithstanding various reports on the process of establishing age-friendly programmes in non-urban settings ( e.g. Bronstein, McCallion and Kramer 2006), most discussion focuses on city contexts ( e.g. Netherland, Finkelstein and Gardner 2011).…”
Section: Age-friendly Communities: the Debate So Farmentioning
confidence: 99%
“…The remaining articles focused specifically on Native American education program such as using talking circles for breast health education and using the multidimensional health locus of control to improve education in the state (Egan et al, 2009; Haozous, Eschiti, Lauderdale, Hill, & Amos, 2010). In fact, there have been very few studies that have focused on rural populations (Aguirre, Wilhelm, & Joshi, 2012; Bronstein, McCallion, & Kramer, 2006; Gutschall, Miller, Mitchell, & Lawrence, 2009; Murphy-Southwick & McBride, 2006; Scala, 2003; Weinert & Hill, 2005). One early study by Scala (2003) reported that “older people living in rural areas face unique challenges, not only in accessing benefits and services, but also in gathering information about programs that can help them.” However, it remains unclear why engagement in healthy behaviors remains such a challenge for many older Oklahomans.…”
Section: Literature Reviewmentioning
confidence: 99%